Aligning Technology and Market Drivers in an Open Source Standards Testing Program. - Bauer, Rick; Milford, Ron; Zhen, Li (Computer (00189162), 2014)
In creating the Open Networking Foundation's conformance testing program for the OpenFlow networking specification, economic, technological, and market drivers must be harmonized, allowing for the simultaneous development of consumer confidence, industry competition, and trustworthy product validation.